How Solidarity Influences Political Actors to Manage the Refugee Crisis: the Case of Proactiva Open Arms - Gemma Álvarez-Jiménez; Maria Padrós-Cuxart (RIMCIS, 2017)
Europe is facing the worst humanitarian crisis since World War II, and the Mare Nostrum has become the path that millions of people are using to flee from the armed conflict, especially since the Syrian war began in March 2011. In this sense, according to the United Nations High Commissioner for Refugees (UNHCR), 1,014,973 people arrived to Greece, Italy and Spain by sea in 2015. Nevertheless, the Mediterranean area has become the scene of not only a humanitarian crisis but also citizens’ solidarity. In this sense, Proactiva Open Arms, an NGO mostly formed by lifeguards, has helped 135,000 people to reach the coast safely, 10,273 of whom sailed in wandering boats. Of these individuals, 475 fell into the water and 9,067 were trapped on the cliffs. Proactiva Open Arms’ work has driven European and Greek authorities to respond to refugees. In this paper, we analyse through this case how solidarity among civil citizens can change political actions and encourage other citizens to act in solidarity, as part of the H2020 European funded research project SOLIDUS.